Enhanced Neutrophil Immune Homeostasis Due to Deletion of PHLPP - Ran, Taojing; Zhang, Yao; Diao, Na; Geng, Shuo; Chen, Keqiang; Lee, Christina; Li, Liwu (Frontiers in Immunology, 2019)
Neutrophils are known to adopt dynamic and distinct functional phenotypes involved in the modulation of inflammation and immune homeostasis. However, inter-cellular signaling mechanisms that govern neutrophil polarization dynamics are not well understood. Employing a novel model of PHLPP deficient mice, we examined how neutrophils deficient in PHLPP may uniquely modulate immune defense and the host response during acute colitis. We found that PHLPP−/− mice were protected from dextran sodium sulfate (DSS)-induced septic colitis characterized by minimal body weight-loss, alleviated colon tissue destruction and reduced clinical symptoms. PHLPP−/− neutrophils have enhanced immune homeostasis as compared to WT neutrophils, reflected in enhanced migratory capacity toward chemoattractants, and reduced expression of inflammatory mediators due to elevated phosphorylation of AKT, STAT1, and ERK. Further, adoptive transfer of PHLPP deficient neutrophils to WT mice is sufficient to potently alleviate the severity of DSS-induced colitis. Our data reveal that PHLPP deficient neutrophils can be uniquely reprogrammed to a state conducive to host inflammation resolution. As a consequence, PHLPP−/− neutrophils can effectively transfer immune homeostasis in mice subjected to acute colitis. Our findings hold significant and novel insights into the mechanisms by which neutrophils can be effectively reprogrammed into a homeostatic state conducive for treating acute injuries such as septic colitis.